Assessment of Iron Concentration in Legumes, Seeds and Meats in Wad-Medni Markets, Sudan - . Alobied1, Omer A; G. Younis 2, Ahmed (Gezira Journal of Engineering and Applied Sciences, 2019)
Micronutrients are essential element needed in small amounts for adequate human nutrition and include the element iron. These mineral are essential to human should have an adequate supply of iron to prevent iron deficiency anemia. The present study is aiming to determination the concentration of iron in variety of foods using the atomic absorption spectrophotometric (AAS), colorimetric and spectrophotometric methods in Wad Medani, Gezira State, Sudan. All samples were collected from Wad Medani, City markets. The results of the samples of Triticum, Setaria , Sorghum bicolor, Cicer arietinum, Vicafaba, Vignanmbellala , Meat Ckicks,  Beef, Sheep meat made by the AAs  were, 1.97, 2.09, 2.00, 3.11, 2.98, 3.19, 2.12, 3.76, 3.15, respectively. The results of calorimetric method of Triticum, Setaria , Sorghum bicolor , Cicer arietinum, Vicafaba, Vigna nmbellala , Meat of Ckicks,  Beef,  and Sheep showed the following  2.01, 2.19, 2.07, 3.54, 3.43, 3.23, 2.78, 4.13, 3.22, respectively. The results of spectrophotometric method of Triticum, Setaria , Sorghum bicolor , Cicer  arietinum, Vicafaba, Vigna nmbellala , Meats of  Ckicks,  Beef and  Sheep gave, 1.88, 2.21, 1.90, 3.07, 3.33, 3.65, 2.70, 3.88, 3.17 , respectively.  The results also showed that legumes contain the highest concentration of iron followed by meats. However the iron concentration in fruits and vegetables is almost equal but less than the concentration in meats . The results also  showed that seeds had the lowest concentrations of iron. On the other hand the results it was found  that there was no significant difference between the three methods of analysis used ,according to test of (One-way ANOVA) ((P<0,05)).